Erosion rates on subalpine paleosurfaces in the western Mediterranean by in-situ 10Be concentrations in granites: implications for surface processes and long-term landscape evolution in Corsica (France) - Kuhlemann, J.; van der Borg, K.; Bons, P.; Danišík, Martin; Frisch, W. (Springer Verlag, 2008)
A study of erosion rates by in-situ 10Be concentrations in granites of Miocene high-elevation paleosurfaces in Corsica indicates maximum erosion rates between 8 and 24 mm/kyear. The regional distribution of measured erosion rates indicates that the local climatic conditions, namely precipitation, the petrographic composition of granites, and the degree of brittle deformation govern erosion rates. Chemical erosion dominates even at elevations around 2,000 m in presently subalpine climate conditions. Field evidence indicates that erosion operates by continuous dissolution and/or disintegration to grains (grusification). The erosion rates are relatively high with respect to the preservation of inferred Early Miocene landscapes. We infer temporal burial in the Middle Miocene and significantly lower erosion rates in the Neogene until ~3 Ma to explain the preservation of paleosurfaces, in line with fission track data. Valley incision rates that are a magnitude higher than erosion rates on summit surfaces result in relief enhancement and long-term isostatic surface uplift. On the other hand, widening and deepening of valleys by cyclic glaciation progressively destroys the summit surface relics.